2013
DOI: 10.1002/anie.201303544
|View full text |Cite
|
Sign up to set email alerts
|

Propargyl Amides as Irreversible Inhibitors of Cysteine Proteases—A Lesson on the Biological Reactivity of Alkynes

Abstract: Are aliphatic alkynes truly bioorthogonal? In an attempt to prepare clickable ubiquitin derivatives bearing a C‐terminal propargyl amide, two groups have now independently discovered propargylamides to be irreversible inhibitors of cysteine proteases. The unexpected findings demonstrate the unexpected reactivity of alkynes in protein‐templated reactions and introduce a novel class of activity‐based protein probes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Work by Sommer et al revealed that the catalytic triad does not have to be intact for covalent bond formation, indicating a proximity-driven reactivity. 22 Although it was believed that the reactivity of the alkyne resulted from a template effect: recognition of (large) protein fragments driving the formation of the thermodynamically unfavored Markovnikov-type thiovinyl product, 23 here we show that strong enough binding can be achieved with a small molecule recognition part. This study highlights the potential of alkynes as latent electrophiles in irreversible covalent small molecule inhibitors, as demonstrated for cathepsin K (CatK).…”
Section: Introductionmentioning
confidence: 57%
“…Work by Sommer et al revealed that the catalytic triad does not have to be intact for covalent bond formation, indicating a proximity-driven reactivity. 22 Although it was believed that the reactivity of the alkyne resulted from a template effect: recognition of (large) protein fragments driving the formation of the thermodynamically unfavored Markovnikov-type thiovinyl product, 23 here we show that strong enough binding can be achieved with a small molecule recognition part. This study highlights the potential of alkynes as latent electrophiles in irreversible covalent small molecule inhibitors, as demonstrated for cathepsin K (CatK).…”
Section: Introductionmentioning
confidence: 57%
“…The bioorthogonality of terminal alkynes has recently been questioned due to the observed covalent modification of cysteines by propargyl amides [47,48,49 ]. Ubiquitin propargylated at the C-terminus (Ub-Prg) inhibits a number of deubiquitinating enzymes (DUBs) through covalent modification of the active-site cysteine nucleophile [47] (Figure 2h).…”
Section: Current Opinion In Chemical Biologymentioning
confidence: 98%
“…They reported the high specificity of the reaction, and deduced that it was driven by the close proximity and alignment of the alkyne and the thiolate ion in the enzyme oxoanion hole, hence driving the reaction forward. This remarkable discovery of irreversible inhibition of cysteine proteases in such a selective manner might find use in activity‐based protein probes, potentially for many protease–substrate partners …”
Section: Thiol‐ene and Thiol‐yne Reactionsmentioning
confidence: 99%